Biogenic signals from plastids and their role in chloroplast development. (25th August 2022) - Liebers, Monique; Cozzi, Carolina; Uecker, Finia; Chambon, Louise; Blanvillain, Robert; Pfannschmidt, Thomas
Abstract : This review provides a historical survey of the field of biogenic plastid signals, critically reflects its role in chloroplast biogenesis, and summarizes the current knowledge into a coherent working model. Abstract: Plant seeds do not contain differentiated chloroplasts. Upon germination, the seedlings thus need to gain photoautotrophy before storage energies are depleted. This requires the coordinated expression of photosynthesis genes encoded in nuclear and plastid genomes. Chloroplast biogenesis needs to be additionally coordinated with the light regulation network that controls seedling development. This coordination is achieved by nucleus to plastid signals called anterograde and plastid to nucleus signals termed retrograde. Retrograde signals sent from plastids during initial chloroplast biogenesis are also called biogenic signals. They have been recognized as highly important for proper chloroplast biogenesis and for seedling development. The molecular nature, transport, targets, and signalling function of biogenic signals are, however, under debate. Several studies disproved the involvement of a number of key components that were at the base of initial models of retrograde signalling. New models now propose major roles for a functional feedback between plastid and cytosolic protein homeostasis in signalling plastid dysfunction as well as the action of dually localized nucleo-plastidic proteins that coordinate chloroplast biogenesis with light-dependent control of seedling development. This review provides a survey of the developments in this research field, summarizes the unsolved questions, highlights several recent advances, and discusses potential new working modes.